Efektivitas Metode Mengajar yang Variatif dalam Keberhasilan Pembelajaran Bahasa Inggris - Wulandari, Wita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This research aims to evaluate the effectiveness of varied teaching methods in the success of English learning. By conducting a literature review of various learning theories, teaching models, and previous research, this research investigates the impact of teaching methods that involve variations such as constructivist approaches, active learning, and the use of technology in improving students' understanding, motivation, and English language skills. The research results show that varied teaching methods can make a positive contribution to English learning achievement, while student motivation plays a crucial role. The implication of the results of this research is the need to integrate innovative teaching methods in the development of the English curriculum to achieve optimal learning outcomes.